2012
DOI: 10.1177/1059840512446949
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a School-Based Sexual Abuse Prevention Education Program on the Knowledge and Attitude of High School Girls

Abstract: Sexual abuse has been considered a public health issue because of the various health implications resulting from it. The school nurse has a responsibility in assisting the high school girl to prevent victimization. This study adopted a quasi-experimental design in which a sexual abuse prevention education package was developed and used to educate high school girls in a selected school in Nigeria. Evaluation of the impact of the package revealed a significant increase in the knowledge mean scores of the girls a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 19 publications
3
16
0
2
Order By: Relevance
“…As well in a similar study done by Ogunfowokan and Fajemilehin (2012), on the impact of school-based sexual abuse prevention education program on the knowledge and attitude of high school girls, found that there was significant increase in the knowledge mean scores of the girls at post intervention stage. Similarly, with the study conducted by Gurung et al (2016), on knowledge of sexual harassment among the undergraduate students in Udupi District, the study revealed that 82.4% of the students had average knowledge, 13.2% had good knowledge and 4.4% had poor knowledge on sexual harassment.…”
Section: Discussionsupporting
confidence: 61%
“…As well in a similar study done by Ogunfowokan and Fajemilehin (2012), on the impact of school-based sexual abuse prevention education program on the knowledge and attitude of high school girls, found that there was significant increase in the knowledge mean scores of the girls at post intervention stage. Similarly, with the study conducted by Gurung et al (2016), on knowledge of sexual harassment among the undergraduate students in Udupi District, the study revealed that 82.4% of the students had average knowledge, 13.2% had good knowledge and 4.4% had poor knowledge on sexual harassment.…”
Section: Discussionsupporting
confidence: 61%
“…For example, Cook () highlights the discordance between safe sex education messages that emphasise individual choice and responsibility and the complexities of condom negotiation that is intricately interweaved with social expectations of appropriate femininity. Ogunfowokan and Fajemilehin () argue that sexual abuse prevention education programmes aimed at schoolgirls need to be supported by the ‘correction’ of ‘myths of sexual abuse …. in the larger society’ (459).…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence to suggest campaigns are effective in enhancing viewers knowledge (Rheingold, Campbell, Self-Brown, de Arellano, Resnick, & Kilpatrick (2007). For example, Ogunfowokan and Fajemilehin (2012) gave female school students a sexual abuse prevention education package and found whilst this increased knowledge about sexual abuse, no significant change was found in their attitudes.…”
Section: Methodsmentioning
confidence: 99%